2003
DOI: 10.1115/1.1602708
|View full text |Cite
|
Sign up to set email alerts
|

Pumpless Loop for Narrow Channel and Micro-Channel Boiling

Abstract: A compact cooling system is examined which capitalizes upon fluid density differences between two vertical, parallel, interconnected tubes to achieve a pumpless cooling loop. A heat-dissipating device is incorporated into a boiler at the bottom of the hot tube. The large density differences between the two tubes produces a substantial nonequilibrium in hydrostatic pressure, drawing liquid downwards through the cold tube as a two-phase mixture is released upwards in the hot tube. Cooling with this pumpless loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…In fact, annular flow was the dominant regime for most medium-and high-flux conditions. This drastic difference between two-phase flow patterns for R134a and water is explained by the low surface tension of R134a producing far smaller bubbles than in water [20]. Very small bubbles are far more apt to travel discretely along a micro-channel before coalescing into long bubbles, thus enabling the bubbly and slug flow regimes to be more prevalent in refrigerant microchannel flow.…”
Section: Flow Visualization Resultsmentioning
confidence: 98%
“…In fact, annular flow was the dominant regime for most medium-and high-flux conditions. This drastic difference between two-phase flow patterns for R134a and water is explained by the low surface tension of R134a producing far smaller bubbles than in water [20]. Very small bubbles are far more apt to travel discretely along a micro-channel before coalescing into long bubbles, thus enabling the bubbly and slug flow regimes to be more prevalent in refrigerant microchannel flow.…”
Section: Flow Visualization Resultsmentioning
confidence: 98%
“…The model has been successful at predicting flow boiling pressure drop of R-113 in a heat sink containing 510 circular micro-channels [17], [19]. On the other hand, a recent study by Mukherjee and Mudawar [30] revealed several fundamental differences in flow boiling behavior in micro-channels between water and FC-72; the latter is a fluorochemical coolant with thermophysical properties fairly similar to those of R-113. Their results reveal the low surface tension and small contact angle of fluorochemicals produce bubble departure diameters that are one to two orders of magnitude smaller than those for water.…”
Section: B Results and Discussionmentioning
confidence: 97%
“…The boundary condition for Wall A of the unit cell is (30) and all other unit cell boundaries are assumed adiabatic.…”
Section: ) Mechanical Considerationsmentioning
confidence: 99%
“…Mukherjee and Mudawar [160,161] developed a new passive cooling technique that can yield far better cooling rates than thermosyphons. The system they developed utilizes fluid density 041002-24 / Vol.…”
Section: Parallel-channel Enhancement: Smart Pumplessmentioning
confidence: 99%
“…To assess the effectiveness of a microchannel boiler at both overcoming these pressure gradients and achieving superior cooling performance compared to thermosyphons, Mukherjee and Mudawar [160,161] tested this concept with both FC-72 and water by varying the "boiler gap" from 0.051 to 21.46 mm as well as using boiler surfaces with vertical microchannels. For large gaps, CHF was fairly insensitive to gap width for both fluids.…”
Section: Parallel-channel Enhancement: Smart Pumplessmentioning
confidence: 99%